2019
DOI: 10.1021/acs.iecr.8b06081
|View full text |Cite
|
Sign up to set email alerts
|

Pinning Down the Water Transport Mechanism in Graphene Oxide Pervaporation Desalination Membranes

Abstract: Graphene oxide (GO) based membranes have attracted considerable interest in desalination and organic dehydration. However, the concern on their stability in water medium still hampers their practical application. In this work, we fabricated a series of GO composite membranes via filtration coating on different substrates, and tested these membranes for their pervaporation desalination performance. We discovered the water productivity was independent of the GO layer thickness (in the GO loading range of 0.034 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The literature suggests the emerging of other less explored applications. Recent GO membranes provide better performances in MD 16,17 and pervaporation 145,146 desalination process, as well as in fouling reduction when combined with silver nanoparticles 68 and in thin-lm nanocomposite membranes. 88 Applications in MD and pervaporation membranes and the role of graphene and GO in improving these processes is a promising direction, which certainly deserves more in-depth consideration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature suggests the emerging of other less explored applications. Recent GO membranes provide better performances in MD 16,17 and pervaporation 145,146 desalination process, as well as in fouling reduction when combined with silver nanoparticles 68 and in thin-lm nanocomposite membranes. 88 Applications in MD and pervaporation membranes and the role of graphene and GO in improving these processes is a promising direction, which certainly deserves more in-depth consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Pervaporation is an alternative process for liquid mixture separation by using nonporous membranes that could have benets from the use of graphene or GO membranes. 145 GO composite membranes fabricated by ltration on different substrates were tested relatively to pervaporation desalination performance, 146 showing no dependence on the GO layer thickness, a stable desalination performance with 99.99% salt rejection for over 50 hours of continuous brine desalination, and 67 L m À2 h À1 with 70 C feed. It was determined that the transition of a liquid to vapor mainly took place at the top few layers of the GO laminates, and water transfer across the membrane occurred in their vapor form.…”
Section: Membrane Distillation and Pervaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…4b) to match the high water fluxes obtained in experiments, otherwise water evaporation would be abnormally slow. However, Li, et al120 proposed a four-stage transport mechanism as shown in Figure2.4c where the phase transition took place inside the GO nanochannels, so that it explained the unchanged flux with different number of GO layers. A more recent MD study (Figure2.4d) showed that the phase transition occurred at the permeate surface of GE membrane for the separation of ethanol and water.…”
mentioning
confidence: 99%
“…Figure 2.4. (a and b) Schematic illustrations of water transport mechanisms inside GO membranes for pervaporation; 119 (c) Schematic diagram of water transport and salt rejection in GO membranes for pervaporation;120 (d) Snapshot of MD simulations for ethanol/water mixture separation using pervaporation through GE nanochannels, where while, red, and green sticks represent hydrogen, oxygen, and carbon atoms respectively 121. …”
mentioning
confidence: 99%